Wallace & Gromit : The curse of the were-rabbit - Box, Steve; Park, Nick.; Sallis, Peter; Fiennes, Ralph; Bonham Carter, Helena, 1966-; Kay, Peter, 1973-; Smith, Nicholas, 1934-2015.; DreamWorks Home Entertainment (Firm); Universal Studios Home Entertainment (Firm) (Universal City, Calif. : DreamWorks Home Entertainment : Distributed by Universal Studios Home Entertainment, 2006)
It's 'veggie-mania' in Wallace and Gromit's neighborhood. The two enterprising friends are cashing in with their humane pest-control outfit, "Anti-Pesto." With only days to go before the annual Giant Vegetable Competition they find that their business is booming. They come to find out that running a "humane" pest control outfit can have its drawbacks. Suddenly, a large and mysterious veg-ravaging "beast" begins attacking the town's sacred vegetable plots at night. The competition hostess, Lady Tottington, commissions Anti-Pesto to catch the beast and save the day. But Victor Quartermaine would rather shoot the beast and secure the position of local hero - not to mention Lady Tottingon's hand in marriage.
Title from container.
Full screen (1.33:1) presentation
Originally released as a motion picture in 2005.
Special features include: Behind-the-scenes fun, including "How to build a bunny"; Aardman short film "Stagefright" ; Deleted scenes ; Clayful activities; Games; Printables.
Directors of photography, Tristan Oliver, Dave Alex Riddett ; editors, David McCormick, Gregory Perler ; art directors, Alastair Green, Sarah Hauldren, Matt Perry ; production designer, Phil Lewis ; visual effects supervisor, Paddy Eason.
Voices: Peter Sallis, Ralph Fiennes, Helena Bonham Carter, Peter Kay, Nicholas Smith.
Keywords: Pests -- Control -- Drama; Contests -- Drama; Friendship -- Drama; Children's films; Animated films; Comedy films; Feature films; Films for the hearing impaired